Experimental and feasibility assessment of biogas production by anaerobic digestion of fruit and vegetable waste from Joburg Market. (May 2018) - Masebinu, S.O.; Akinlabi, E.T.; Muzenda, E.; Aboyade, A.O.; Mbohwa, C.
Highlights: Appropriate fruit to vegetable waste mix can reduce anaerobic digestion instability. Optimum biogas yield was achieved at a fruit to vegetable ratio of 2.2:2.8. Buying electricity and upgrading all biogas to biomethane is economically viable. Abstract: Substrate-induced instability of anaerobic digestion from fruit and vegetable waste (FVW) results in low biogas yield. In this study, substrate management through fruit to vegetable mix ratio in a two-stage semi-continuous digester was investigated as a pathway for optimality of yield. The experiment conducted over 105 days with 62.52 kg of FVWs sourced from Joburg Market, South Africa showed that a stable process was achieved at a fruit to vegetable waste mix ratio of 2.2:2.8. At this ratio, optimal organic loading rate ranged between 2.68 and 2.97 kg VS/m 3 -d which resulted in a specific biogas yield of 0.87 Nm 3 /kg VS with 57.58% methane on average. The results of the experimental study were used as a feasibility assessment for a full-scale 45 tonnes/d plant for Joburg Market considering three energy pathways. The plant will produce 1, 605, 455 Nm 3 /y of biogas with the potential for offsetting 15.2% of the Joburg Market energy demand. Conversion of all biogas to biomethane was the most economically attractive energy pathway with a net present value of 2, 428, 021, an internal rate of return of 16.90% and a simple payback period of 6.17 years. This route avoided the greenhouse gas emission of 12, 393 tonnes CO2, eq. The study shows that the anaerobic digestion of FVWs as sole substrate is possible with financial and environmental attractiveness.